THE EFFECTIVENESS OF PEER RIVIEW TECHNIQUE IN IMPROVING THE STUDENTS’ WRITING ABILITY IN RECOUNT TEXT AT JUNIOR HIGH SCHOOL LEVEL - Hendra Suryadi; Ahmad Taufik (Jurnal Ilmiah Global Education, 2023)
The objective of this research was aimed to investigate the effectiveness of peer reviewing in improving the students’ writing ability in recount text.   The method of the research was quasi-experimental design with control and experimental group and post-test only. The population of this research was the entire eight grade students of SMPN 1 Pringgarata. The cluster random sampling was used in the sampling technique. There were two classes of eight grade students as the sample of this research. They were VIII A that consists of 32 students as the control class and VIII B that consists of 30 students as the experimental class. Test and questionnaire were the instruments of this research. The data collected from the tests were analyzed by using independent sample t test and MANOVA through SPSS.   Results show that the independent sample t-test was 0.001 for motivation and 0.000 for the writing ability. Moreover, the result of MANOVA test was 0.000. The results were consulted to the score of the significant value generated Sig. (Pvalue) < α = 0.05. Thus, Ho was rejected and Ha was accepted. In other words, the result of the study revealed that peer review gave significant effect to the students’ wriying ability in recount text. It can be concluded that there is a significant effect to the students’ writing ability who taught using peer review.